Public Response to the 2024 Presidential Election Results in Purba Sinomba Village, Padang Bolak District - April Partahian Dalimunthe; Farhan Indra (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to analyze the response of the Purba Sinomba Village community to the results of the 2024 Presidential Election, with a focus on the socio-political dynamics that occur in rural areas. Using a descriptive qualitative approach, data were collected through in-depth interviews and observations of community political participation. The results of the study indicate that despite political polarization and dissatisfaction with the election results, the community tends to prioritize social harmony by respecting each other's choices, with the role of local figures such as village officials, religious leaders and youth leaders as important mediators in easing tensions. In addition, disinformation circulating through social media worsens the situation, especially due to the low political and digital literacy among rural communities. This study suggests the need to improve political and digital literacy to reduce the negative impact of invalid information, as well as strengthen the role of local figures in maintaining social stability post-election.